Upaya Meningkatkan Kosakata Bahasa Inggris Menggunakan Metode Bernyanyi pada Anak Usia Dini Kelas B di Paud An-Nur Pontianak Timur - Nadia Elsa U D; Yuniarti Yuniarti; Diana Diana (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This research is motivated by problems related to obstacles in the ability to master English vocabulary, in which children find it very difficult to memorize English words, the accuracy of pronouncing English vocabulary delivered by the teacher, especially when memorizing vocabulary with more than one syllable as well as the presence of errors or inaccuracies in pronunciation and in answering the intended meaning during English learning activities. The reality found in the field shows that the children’s English vocabulary ability has not yet demonstrated significant success. Out of a total of 12 students, only 4 children have the expected level of ability. The purpose of this study is to describe efforts to improve children’s English vocabulary using the singing method. The benefits of this research include improving students’ English vocabulary skills, encouraging teachers to become more creative and innovative, and contributing to school quality improvement. This study uses Classroom Action Research (CAR) with two cycles, and each cycle consists of two meetings. The research was conducted at PAUD An-Nur located in East Pontianak. The improvement actions implemented showed satisfactory results. In Cycle I, children’s ability to pronounce English vocabulary reached 33%, which was still below the Minimum Mastery Criterion (MMC) of 70%. Furthermore, in Cycle II, the results reached 83%, which was already above the MMC. It can be concluded that the singing method is effective in improving children’s English vocabulary.